2021
DOI: 10.1158/2643-3230.bcd-21-0028
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific Antibodies in Multiple Myeloma: Present and Future

Abstract: Despite many recent advances in therapy, there is still no plateau in overall survival curves in multiple myeloma. Bispecific antibodies are a novel immunotherapeutic approach designed to bind antigens on malignant plasma cells and cytotoxic immune effector cells. Early-phase clinical trials targeting B-cell maturation antigen (BCMA), GPRC5D, and FcRH5 have demonstrated a favorable safety profile, with mainly low-grade cytokine release syndrome, cytopenias, and infections. Although dose escalation is ongoing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 103 publications
(104 reference statements)
0
58
0
2
Order By: Relevance
“…Bispecific antibodies have risen as another exciting novel therapy for triple-class RRMM. Similar to CAR-T, bispecific antibodies function by binding a target on the malignant plasma cells, such as BCMA, GPRC5D, and FcRH5, while simultaneously binding to T cells via CD3 to create an immune synapse leading to immune cell activation and destruction of the cancer cell [ 64 ]. There are currently three bispecific antibodies, each with a different target, currently far in clinical development in MM: teclistamab (anti-CD3/BCMA), cevostamab (anti CD3/FcRH5), and talquetamab (anti-CD3/GPRC5D) [ 64 ].…”
Section: Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Bispecific antibodies have risen as another exciting novel therapy for triple-class RRMM. Similar to CAR-T, bispecific antibodies function by binding a target on the malignant plasma cells, such as BCMA, GPRC5D, and FcRH5, while simultaneously binding to T cells via CD3 to create an immune synapse leading to immune cell activation and destruction of the cancer cell [ 64 ]. There are currently three bispecific antibodies, each with a different target, currently far in clinical development in MM: teclistamab (anti-CD3/BCMA), cevostamab (anti CD3/FcRH5), and talquetamab (anti-CD3/GPRC5D) [ 64 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…Similar to CAR-T, bispecific antibodies function by binding a target on the malignant plasma cells, such as BCMA, GPRC5D, and FcRH5, while simultaneously binding to T cells via CD3 to create an immune synapse leading to immune cell activation and destruction of the cancer cell [ 64 ]. There are currently three bispecific antibodies, each with a different target, currently far in clinical development in MM: teclistamab (anti-CD3/BCMA), cevostamab (anti CD3/FcRH5), and talquetamab (anti-CD3/GPRC5D) [ 64 ]. G protein coupled-receptor class C group 5 member D (GPRC5D) is a cell surface protein of unknown function that is highly expressed on malignant plasma cells.…”
Section: Immunotherapymentioning
confidence: 99%
“…Treatment of MM has advanced significantly over the past decade with the approval of novel agents including proteasome inhibitors (PI) such as bortezomib, carfilzomib, and ixazomib; immunomodulatory drugs (IMiD) such as lenalidomide and pomalidomide; monoclonal antibodies, namely daratumumab, isatuximab, and elotuzumab [ 7 ]; and other newer treatments in development including bispecific antibodies [ 8 ] and chimeric antigen receptor T cell (CAR-T cell) therapies [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, the incidence of MM has increased globally by 126% whereas the age-standardized mortality rate has been steadily falling [ 1 ] due to the utilization of novel agents [e.g., immunomodulatory drugs (IMiDs), the proteasome inhibitors (PIs), monoclonal antibodies, BCL2 inhibitor, etc.] in the treatment of MM [ 2 4 ]. Moreover, high-dose chemotherapy followed by autologous hematopoietic stem cell transplantation (auto-HSCT) is recognized as an effective therapy as consolidation after induction treatment for newly diagnosed MM patients aged less than 65 years [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the disease remains incurable, and considerable patients are eventually subject to disease relapse. Several approaches concentrating on different stages of MM treatment have been developed to down-regulate the incidence of disease progression, including improving the induction of chemotherapy prior to auto-HSCT by combining novel agents [ 2 4 ], and applying maintenance treatment with IMiDs or PIs following auto-HSCT [ 6 8 ]. Furthermore, existing evidence revealed that MM patients might benefit from intensifying pre-transplantation conditioning chemotherapy to mitigate disease relapse and prolong survivals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%